Finding alternatives to swidden agriculture: does agroforestry improve livelihood options and reduce pressure on existing forest? - Rahman, S.A.; Jacobsen, J.B.; Healey, J.R.; Roshetko, James M.; Sunderland, Terry C.H. (Springer, 2017)
Swidden cultivation can contribute to deforestation and land degradation, which can subsequently result in a number of serious environmental problems. This paper examines the economic and social potential of agroforestry systems and the barriers to their widespread adoption, as a land use alternative to swidden cultivation, which may potentially help protect local forest. The Gunung Salak valley in West Java, Indonesia is presented as a case study. Based on farmers' and experts' assessment, costs and benefits have been estimated, which show that the two investigated agroforestry systems have higher net present value and benefit-cost ratio (B/C) than the two swidden cultivation systems. Tree ownership also creates more permanent rights to farmland and is prestigious in the community. Agroforestry products (fruit, vegetables etc.) have high monetary value and help strengthen social cohesion when shared with neighbors. However, farmers are reluctant to implement agroforestry. Stated reasons are related to both culture and capacity. Farmers practicing agroforestry are less involved in forest clearing and forest products collection than swidden farmers indicating that it may contribute positively to conservation of local forests. Increasing the adoption of agroforestry farming in the study area will require support to overcome capacity constraints.